THE SACRED LOCUS OF LAKE KHUKO: A RITUAL AND RITUAL COMPLEX, ETYMOLOGY AND RELIGIOUS SYMBOLISM - Stybin, Vitalij Vladimirovic (History, Archeology and Ethnography of the Caucasus, 2023)
A number of special ritual practices of calling rain among the Black Sea Circassians-Shapsugs of the city of Sochi in the Krasnodar Territory are associated with the locus of Lake Huko, located on the Greater Caucasus Range near the border with the Republic of Adygea. In this article, based on field research, ethnographic and folklore materials, an attempt is made to explore these practices in relation to the toponymic etymology of the lake and its syncretic religious symbolic meanings.The presence in the ritual practices and etymology of the connection of the lake with the sea and the dolphin may indicate the presence in them of the relic symbols of early Christianity in its "folk" form. This is also hinted at by the “fish” symbolism found near the lake, which, however, requires careful verification of the time of its appearance. This article provides an analysis of the "marine" Christian symbolism in relation to the sacred narrative of Lake Huko. This approach allows us to look at the ritual practices of the Khuko locus from the point of view of the history of religion and the analysis of the sacred landscapes of the ethnographic group of the Black Sea Circassians-Shapsugs, and to highlight the syncretic forms of mixed traditional and Christian symbols that existed
Keywords: ritual practices; rites; Adyghe folklore; Circassians; locus Huko; symbols of Christianity; symbols of Christ; ethnography of the Caucasus; Sochi; Black Sea Adygs-Shapsugs; cultural anthropology